Expatriates Self-Motivation, Competencies, Job Performance and Cultural Adjustment: Empirical Evidence from the ICT Sector in Malaysia - Singh Kartar Singh, Jugindar; Hasnaa Nik Mahmud, Nik (International Journal of Engineering and Technology, 2018)
The purpose of this paper is to investigate the impact of self-motivation and competencies towards job performance of expatriates working within the ICT sector in Malaysia. Additionally, this study examines the mediating effect of cultural adjustment. A survey strategy associated with a quantitative method using a self-administered questionnaire was carried out. Data was collected through simple random sampling from a sample of 301 expatriates. The AMOS software developed for analyzing the Structure Equation Modeling (SEM) was utilized. Emotional and job related competencies were found to have a significant effect on expatriate job performance. However, the impact of self-motivation on job performance was found to be not significant. The findings also supported the role of cultural adjustment as a mediator.  The theoretical framework emerging from this study support the results from some earlier studies and also brings out several new ideas such as the importance of competencies and cultural adjustment. The findings have significantly contributed to the advancement of knowledge as it is evident that expatriate emotional and job related competencies facilitate job performance and cultural adjustment. By investigating self-motivation and competencies, this study informs organizations on ways they can implement improvements in the areas of expatriate hiring, training and support practices. It is recommended that organizations consider both emotional and job related competencies and implement suitable HR policies when selecting, training and motivating the right candidate.
Keywords: Cultural adjustment; performance; expatriate; self-motivation